Challenges in Implementing Early Intervention for Students with Special Needs in Remote Areas: A Case Study of Tioman Island. - Mohamad Haniff Azmi; Khairul Farhah Khairuddin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study explores the challenges of implementing early intervention for Students with Special Needs (SSN) in remote areas, with a specific focus on Tioman Island. This qualitative research employed a case study design and involved in-depth interviews with 12 participants comprising special education teachers, parents, and school administrators. The findings revealed three main challenges: limitations in resources and infrastructure, issues related to human resources and training, and geographical and logistical challenges unique to the island context. The study also documented various adaptive strategies implemented by schools, including the development of teaching and learning materials using local resources, collaboration with the local community, and the use of flexible instructional approaches. The findings suggest the need for a contextualised approach to early intervention implementation in remote areas that takes into account resource constraints and location-specific characteristics. Overall, the results provide important implications for policymakers in designing more effective and context-appropriate early intervention programmes for remote areas in Malaysia.